Prevention and treatment of CCV in patients undergoing cataract phacoemulsification - E. Yu. Yazykova; L. Sh. Ramazanova (Oftalʹmologiâ)
The study was hold on the basis of LLC «Eye Microsurgery» in Astrakhan.Purpose: clinical evaluation the influence of Systane Balance (Alcon) the condition of the «ocular surface comfort» at patients with phaco.Materials and methods. 60 patients took part in the study. 30 men and 30 women aged from 68 to 80 years. After the first survey the patients were divided into two groups by means of random choice (15 men and 15 women in each group). Three days before the surgery Both groups of patients received antibiotics (Vigamox (Alcon) and NSAIDs (Nevanac, Alcon) according to the standard scheme for preoperative preparation (during 3 days before operation). These drugs were also recommended in the postoperative period. Systane Balance (1 drop 2‑3 times a day) was prescribed for the first group in 2 weeks before phaco. The second group didn’t get any artificial tears. Systane Balance had been chosen as an artificial tears as its composition is very close to the natural tear film, compensates the deficiency of the lipid layer that is broken when meibomean gland dysfunction (MGD) thus it prevents from increasing tear film osmolarity and its rupture.Results: In 60% (36 people) SSG was due to dysfunction of the meibomian glands, and 40% (24 people) had a different genesis (endocrine pathology, receiving β-blockers for local and systemic effects, long-term use of drugs containing the preservative benzalkonium chloride, menopause). One week after phacoemulsification all patients of group 1, treated with the drug Sisteyn Balance dramatically decreased the severity of complaints of dry eye, foreign body sensation, burning, lacrimation, blurred vision in comparison with the group without artificial tears One month after surgery, these complaints were even less pronounced. At the same time, subjective complaints in patients of the second group observed significantly more frequently than before surgery.Conclusions. The patients who belong to the senior age group have MGD much more frequently (up to 60%). We received the optimization of the postoperative course, the improvement the quality of life of such patients and prevention from complications is possible in case of Dry Eye treatment, that is associated with MGD, with the help of Systane Balance.